Emerging Imaginaries of Regulation, Control, and Repression - Lippens, Ronnie (Social justice, 2005)
A special issue on emerging imaginaries of regulation, control, and repression. Topics discussed include bourgeois identity and criminality; media images of social exclusion; the feminization of the corporation and the masculinization of the state; the colonial apparatus in 21st-century control; graffiti and resistance in contemporary Colombia; tactics in New York homicide trials in the 1920s; participatory action research, imagined communities, and social justice; the rhetoric of victimhood as a source of oppression; criminals and the pseudo-pacification process; terrorism and antiterrorism terrorism; and transformations of imperial imaginaries.